Posterior Reversible Encephalopathy Syndrome (PRES) in a Patient with Opioid Use Disorder. (17th June 2021) - Tumenta, Terence; Adeyemo, Samuel; Oladeji, Oluwatoyin; Jegede, Oluwole; Laurent, Bordes; Olupona, Tolu
Abstract : Posterior Reversible Encephalopathy Syndrome (PRES) is a characteristic clinical radiographic syndrome with diffuse structural alteration of cerebral white matter secondary to myelin damage with diverse and multifactorial etiologies. It can present with acutely altered mentation, somnolence or occasionally stupor, vision impairment, seizures, and sudden or chronic headaches that are not focal. The pathophysiology remains unclear, but mechanisms involving endothelial injury and dysregulation of cerebral autoregulation have been purported. We report the case of a 36-year-old male with a history of heroin use disorder, who was admitted to our hospital for opioid withdrawal. CT head without contrast and MRI with and without gadolinium showed significant white matter disease in both cerebral hemispheres and cerebellum. He was diagnosed with Posterior Reversible Encephalopathy Syndrome secondary to heroin use and managed on the medical floor in collaboration with the neurology team. His clinical symptoms improved and he was discharged after six weeks. To our knowledge, this case did not present with the risk factors for PRES reported in the literature. For patients with heroin use disorder who present with an altered mental status, PRES should be highly suspected. The diagnosis and management require collaboration between psychiatry and neurology.